Posterior Urethral Valves: Renal Failure and Prenatal Treatment - Daniel P. Casella; Jeffrey J. Tomaszewski; Michael C. Ost (International Journal of Nephrology)
Posterior urethral valves occur in 1 : 5000 live births. Despite the high prevalence, the few children that survive do poorly, with over 50% progressing to ESRD in 10 years. The gold standard for post-natal diagnosis is voiding cystourethrography, while pre-natal diagnosis is dependent on routine screening ultrasonography. Despite the ability to identify features of bladder outlet obstruction early in fetal development, there is no consensus on how to incorporate early detection into current screening protocols. There has yet to be a marker that allows prediction of obstruction in the absence of or prior to radiographic evidence of obstruction. With our current screening strategy, the majority of interventions are performed well after irreversible damage has occurred. Improved mortality and long term morbidity from posterior urethral valves and congenital bladder outlet obstruction will likely remain unchanged until it is possible to intervene prior to the onset of irreversible renal damage. New biologic markers and improved instrumentation will allow for more effective diagnosis and intervention at earlier stages of fetal development.